Analysis of Vitamin C Levels and Antioxidant Activity in Red Dragon Fruit (Hylocereus polyrhizus) - Intan Pratiwi; Suherman Suherman (Universitas Tadulako, 2021)
Research on the analysis of vitamin C levels and antioxidant activity in red dragon fruit (Hylocereus polyrhizus) has been carried out using UV-Vis spectrophotometry. In this study, fresh dragon fruit flesh was mashed with a blender and the maceration method with 96% absolute ethanol solvent was carried out three times. The meseration results were evaporated using a rotary evaporator to obtain a thick extract. In the DPPH free radical scavenging test and the determination of vitamin C levels in red dragon fruit extract (Hylocereus polyrhizus) the original vitamin C was used as a comparison. In determining the levels of vitamin C in the extract, the extract solution was made with a concentration of 1000 ppm which was determined by UV-Vis spectrophotometry, showing that the levels of vitamin C in the extract of red dragon fruit (Hylocereus polyrhizus) had an average vitamin C content of 31.413 mg/100g. In the antioxidant activity test of the extract solution, various concentrations were made, namely 50 ppm, 100 ppm, 150 ppm, 200 ppm and 250 ppm, the average percentage of antioxidant activity was 19,859